Red river and associated faults, Yunnan Province, China : quaternary geology, slip rates, and seismic hazard - Yuan, Han (2013)
The 900-km-long right-slip Red River fault of southernmost China and northern Vietnam is a profound structural discontinuity that is mechanically associated with the collision of the Indian and Eurasian plates. Although history records no large earthquakes resulting from slippage along at least the principal segment of the fault in China, youthful landforms and disruptions of young sedimentary rocks indicate that it has generated large earthquakes during the Pleistocene and Holocene epochs. The historic quiescence thus must be regarded as being indicative of a current seismic gap, although the recurrence interval between major earthquakes is evidently much longer than for many other major active fault systems.